2021
DOI: 10.1016/j.sjbs.2021.04.074
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting effects of maize residue, coal gas residue and their biochars on nutrient mineralization, enzyme activities and CO2 emissions in sandy loess soil

Abstract: Mismanagement of crop straw and coal gas residue threatens the atmosphere and the economy. Nevertheless, thermal-pyrolysis is an option for management that turns bio-waste into biochar; its viability and adoption by the public as soil amendments is dependent on the agronomic and environmental values compared between biochar and the raw materials. We undertook a 60-day short-term analysis to assess the impact of various wastes and biochars, as well as inorganic nutrients (N), on carbon dioxide (CO 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…However, there were also some studies that reported little effect of biochar on soil nutrients [32] or negative effects, such as Sun et al [27] who showed that compared with B0 (no biochar), the SOC content presented a 14.0% decrease with B30 (30 Mg ha −1 biochar). The inconsistency could be attributed to biochar feedstocks and characteristics [33], the application ratio of biochar [34], plant types [35] and soil properties [36].…”
Section: Introductionmentioning
confidence: 99%
“…However, there were also some studies that reported little effect of biochar on soil nutrients [32] or negative effects, such as Sun et al [27] who showed that compared with B0 (no biochar), the SOC content presented a 14.0% decrease with B30 (30 Mg ha −1 biochar). The inconsistency could be attributed to biochar feedstocks and characteristics [33], the application ratio of biochar [34], plant types [35] and soil properties [36].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, allowing the biochar from different particle sizes having different applications depending on their characteristics. The larger particle sizes could be used in iron sintering [104] and to make H 2 through steam activation [69,83,91] Lower particle sized char, with its more irregular shape [100], which along with an increased microporosity has higher absorbent properties and would be more useful in environmental applications such as water storage in soils and water purification [105][106][107]. Biochar produced through pyrolysis of ASR and other heterogenous materials may have similar positive effects on soil properties and water purification as traditional homogenous feedstocks, however this still has to be proved as research into this area is limited.…”
Section: Heterogeneous Biochar Feedstock: Automotive Shredder Residuementioning
confidence: 99%
“…Biochar produced through pyrolysis of ASR and other heterogenous materials may have similar positive effects on soil properties and water purification as traditional homogenous feedstocks, however this still has to be proved as research into this area is limited. Recent laboratory studies indicated that coal residue biochar can increase SOC (Soil Organic Carbon) and TN (Total Nitrogen) concentration, when compared with maize biomass biochar, fresh residues and control soil [107], which could enhance crop growth. A supposition could be put forward that this would be true for heterogeneous feedstocks.…”
Section: Heterogeneous Biochar Feedstock: Automotive Shredder Residuementioning
confidence: 99%